Predicative possession in Caquinte (Campa-Arawak) - Castillo Ramirez, Antonio G. (2015)
In this paper we describe possessive constructions in caquinte, an Amazonian language spoken in the departments of Junin and Cuzco. Based on data collected in the field, we will analyze the expressions of predicative or sentence-level possession. In this document, we will see that the Caquinte language categorizes its names based on their alienability, a criterion that involves both grammatical and cultural features. We will distinguish the names that need to be possessed (inalienable) from the ones that do not need a possessor (alienable) and from those that are not used to be possessed. As the main focus, we will describe the semantics and morphosyntax of the verbs that express possession. Finally, we will analyze the noun incorporation and verbal aplicativization processes, both involved in the possession dominion.